1997
DOI: 10.2166/wst.1997.0065
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and degradation of filtrated organic particulates in a biofilm reactor under anoxic and aerobic conditions

Abstract: Two experiments were performed in order to investigate the anoxic and the aerobic degradation of filtrated organic matter in a biofilter. In submerged lab. scale reactors with Biocarbone media as filter material, accumulated particulate organic matter from pre-settled wastewater served as the only carbon source for anoxic and aerobic degradation respectively. In order to utilise the accumulated organic matter, the bacteria in the biofilm had to produce extracellular hydrolytic enzymes for the hydrolysis proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This hypothesis is supported by experimental results from Janning et al (1997). According to the assumptions underlying the model concept (assumption (5)) readily biodegradable organic matter from hydrolysis is modelled as being instantaneously transferred into the bulk liquid.…”
Section: Description Of Biokinetic Processes In the Bio®lmð Process Mmentioning
confidence: 65%
“…This hypothesis is supported by experimental results from Janning et al (1997). According to the assumptions underlying the model concept (assumption (5)) readily biodegradable organic matter from hydrolysis is modelled as being instantaneously transferred into the bulk liquid.…”
Section: Description Of Biokinetic Processes In the Bio®lmð Process Mmentioning
confidence: 65%
“…In recent years an increasing interest in the modeling of the endogenous subprocess, in particular for activated sludge processes, has been developed (Beeftink et al, 1990;Dold et al, 1980;Droste, 1996;Horn and Hempel 1997;Janning et al, 1997;Keesman et al, 1998;Pirt, 1965;Ratsak et al, 1996;Spanjers, 1993;Sykes, 1991;Torrijos et al, 1994;Wentzel et al, 1992;Yuan and Stenstrom, 1996). In microbiological literature endogenous respiration is defined in terms of maintenance: it occurs when there is no observed substrate consumption and when maintenance ATP is obtained from biomass degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have suggested that extracellular enzymes have to be released by the biofilm in order to hydrolyse the particulate organic matter (Larsen et al, 1994;Hu et al, 1996). Subsequent research (Janning et al, 1997;Janning et al, 1998) has shown that the hydrolysis process occurs as the only process with wastewater particulates and that only 10% of the particles accumulated on the biofilm was effectively hydrolysed in 12-hour long experiments. It may hi!…”
Section: Hydrolysis Of Particulate Organic Mattermentioning
confidence: 99%